1989
DOI: 10.2134/jpa1989.0357
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Chemical Composition and Ruminal Fermentability of Corn Whole Plant, Ear, and Stover as Affected by Maturity

Abstract: The nutritive value of corn (Zea mays L.) grain remains relatively constant; nutrient content and digestibility, however, may vary significantly in the remaining corn plant parts. Understanding of the relationships between plant maturity and plant component yield, nutrient content, and digestibility is important for prudent harvest management of nongrain corn parts. Six corn hybrids planted at two locations (Nampa, ID, and Modesto, CA) were used to evaluate the effects of maturity on yield, chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
3
16

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 16 publications
12
56
3
16
Order By: Relevance
“…The increase in starch content of whole-crop maize and the parallel reduction in the content of water-soluble carbohydrate, with the later harvest, were in accord with Hunt et al (1989), Filya (2004) and Lynch et al (2012). This can be related to the increased contribution of cob to the whole-crop DM yield and accumulation of starch in the grains during the maturation period (Cone et al 2008, Lynch et al 2012 (Lynch et al 2012(Lynch et al , 2013.…”
Section: Discussionmentioning
confidence: 54%
“…The increase in starch content of whole-crop maize and the parallel reduction in the content of water-soluble carbohydrate, with the later harvest, were in accord with Hunt et al (1989), Filya (2004) and Lynch et al (2012). This can be related to the increased contribution of cob to the whole-crop DM yield and accumulation of starch in the grains during the maturation period (Cone et al 2008, Lynch et al 2012 (Lynch et al 2012(Lynch et al , 2013.…”
Section: Discussionmentioning
confidence: 54%
“…(Table 3). Hunt et al (1992) found out that NDF of hybrids varied from 417 to 490 g/kg and ADF from to 239 to 283 g/kg. The silage maize producer may wish to consider hybrid quality characteristics in addition to DM yields before selecting a hybrid (Graybill et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Meager digestibility and poorer intake are usually linked with high fiber content and low protein content. As the crops get mature, dry matter and cell wall constituents raise and protein contents drop [9]. Realizing the fact that Pakistan and especially Khyber Pakhtunkhwa region is lacking of green fodder for its animals both in term of quantity and quality-and keeping in view the above facts an experiment entitled effect of different nitrogen levels and cutting stages on crude protein, crude fiber, dry matter and green fodder yield of oat (Avena sativa L.) was designed to investigate the optimum level of nitrogen and best cutting stage harness a reasonable nutritive green fodder for the animals.…”
Section: Introductionmentioning
confidence: 99%